MAHARAJAH’S RESTRUCTURING VIA, ACQUISITION: A CRITICAL CASE ANALYSIS - Pallavi, Baghel (INTI International University, 2022)
The acquisition of Air India- a prodigal child by the Tata Group is the talk of the town. Air India was a prosperous airline till it was with its Indian aviator- JRD Tata. It started suffering losses since 2007-08, all turnaround and financial restructuring plans failed to work out and the Government had to pay Rs. 20 crore per day to keep it alive. Its disinvestment failed in 2017 but finally in 2020 Government sweetened the deal for the buyers by selling 100% of its stake in the airlines and Tata Group won the bid. This research paper deeply analyzes the case of acquisition of Air India by the Tatas, discovers the facts which led to its catastrophe, examines the consequences of its failure, records the issues which came in the way of its sale, assesses the viability of its restructuring via- 100 per cent disinvestment plan and sheds light on the gravity of business restructuring mechanism. It also examines the facts, issues and decision of the case. This case is very important as Air India was once a pinnacle airlines of India and also amongst the major international airlines of the world. It is a prominent case to underscore the significance of business restructuring tools for the rehabilitation of sick yet viable companies and the economy. The World Bank’s research also recognizes that effective corporate reforms can reduce the cost of credit, increase timely repayments and lower liquidate rate amongst economically distressed companies. The researcher in this study evinces that the companies should not rely on debt and should keep a close eye on the debt because debt is one of the prime reasons for the collapse of a company and economy. Air India’s restructuring is though a herculean task for the Tatas but still it is the best route for its resurrection as the acquisition will help in using the synergies of both the companies and at the end of the day it will be beneficial for the Indian Economy as a whole. The researcher eventually suggests that the Tatas should try to reduce costs, debt burden, make best use of available talent and resources, incorporate new technologies, expand its operations and implement an effective framework. The study also puts forward that due to the aftermath of COVID-19, large number of small and medium sized companies have become sick and are suffering losses, so for them corporate restructuring is the solution to revive. This novel research study will prove to be a principal research study for the researchers, policy makers and professionals in conducting future researches to study the impact of business restructuring (via, takeover of Air India). Since, Air India is recently acquired in January, 2022 so the effect can’t be studied at the present stage. A comparison of various ratios and statistical tools before and after restructuring can be done in the following years to measure the benefits of restructuring of Air India.